Housing System, Challenges, and Perspectives - The Case of Georgia - Sophio Barnabishvili (European Scientific Journal, ESJ, 2023)
Expired or Dilapidated multi-apartment buildings are one of the main problems in post-Soviet countries. Although different countries have periodically developed different ways to solve the problem, it has not been possible to solve it until new reform, because the analysis of the current practice shows that the only way to solve the problem is to dismantle the dilapidated multi-apartment residential buildings and build new ones instead. The present article discusses the history of the development of the housing system in Georgia, the preconditions of the housing crisis, the existing social programs in Tbilisi Municipality, and the reform aimed at the gradual replacement of dilapidated houses. The article focuses on the international experience related to housing fund management, including in the countries of the post-Soviet space. The scope of powers of the state, municipality, and owners, prerequisites for the replacement of damaged residential houses, and decision-making procedure are discussed. The replacement process, the general characteristics of the multi-unit residential buildings subject to replacement, and the challenges the social program faces are described.